Trends and drivers of African fossil fuel CO2 emissions 1990–2017 - Lacour M Ayompe; Steven J Davis; Benis N Egoh (Environmental Research Letters, 2021)
International efforts to avoid dangerous climate change aim for global carbon dioxide (CO _2 ) emissions to be net-zero by midcentury. Such a goal will require both drastically reducing emissions from high-income countries and avoiding large increases in emissions from still-developing countries. Yet most analyses focus on rich-country emissions reductions, with much less attention to trends in low-income countries. Here, we use a Kaya framework to analyze patterns and trends in CO _2 emissions from the combustion of fossil fuels in Africa between 1990 and 2017. In total, African CO _2 emissions were just 4% of global fossil fuel emissions in 2017, or 1185 MtCO _2 , having grown by 4.6% yr ^−1 on average over the period 1990–2017 (cf the global growth rate of 2.2% yr ^−1 over the same period). In 2017, 10 countries accounted for about 87% of the continent’s emissions. Despite modest recent reductions in some countries’ CO _2 emissions, projections of rapid growth of population and per capita GDP will drive future increases in emissions. Indeed, if the continent-wide average growth rate of 2010–2017 persists, by 2030 Africa’s emissions will have risen by ∼30% (to 1545 MtCO _2 ). Moreover, if increases in carbon intensity also continue, Africa’s emissions would be substantially higher. In either case, such growth is at odds with international climate goals. Achieving such goals will require that the energy for African countries’ development instead come from non-emitting sources.